Investigating the influence of ubiquinone blood level on the abilities of children with specific learning disorder - Ehab Ragaa Abdelraouf; Ayman Kilany; Adel F. Hashish; Ola Hosny Gebril; Suzette Ibrahim Helal; Haytham Mohamad Hasan; Neveen Hassan Nashaat (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2018)
Abstract Background Ubiquinone has antioxidant properties and has been linked to cognitive performance in some neuropsychiatric disorders. Its role in specific learning disorder manifestations has not been previously investigated. Therefore, the aim of this study was to measure the blood levels of ubiquinone in a group of children with specific learning disorder in comparison to typically developing children and to investigate the correlation between ubiquinone levels in children with specific learning disorder and some of their intellectual capabilities, reading, spelling and writing performance.  Methods The study included 71 native Arabic speaking children: 31 in the specific learning disorder group and 40 in the typically developing (TD) group. The abilities of the children with specific learning disorder were evaluated by the Stanford-Binet Intelligence Scale-4th edition, the Dyslexia Assessment Test, and the Illinois Test of Psycholinguistic Abilities. The level of ubiquinone was measured in both groups by ELISA. Correlation between some aptitudes of children with specific learning disorder and the ubiquinone level was performed. Results The blood levels of ubiquinone in the children with specific learning disorder group were less than those in the TD group. Correlation analysis revealed a significant positive correlation between ubiquinone and the scores of backward digit span abilities. Conclusions Ubiquinone has a role in the auditory working memory performance of children with specific learning disorder (with impairment in reading). The decreased levels of ubiquinone in this sample of children with specific learning disorder could have participated in the pathogenesis of this disorder.